The moral values and their manifestations of in Muallaqa Zuhair bin Abi Solma - Ismael, Abuhedaia Mohammed; Eldewada, Youisf Ali (Journal of Arabic Language Sciences and Literature, 2022)
This study dealt with the manifestations of moral values ​​in Muallaqa Zuhair bin Abi Solma. The study aimed at highlighting the ethical aspect surrounding the mu'allaqah systems, and to prove that ethics dominated the ideas of poetry when composing the poem, and the importance of the study stems from the importance of ethics and its role in directing the poet towards it in his expression. We followed this inductive descriptive approach, and we drew on the material of the study from the commentaries of the commentator, and the sayings of critics, past and present, from the results of the study that, Zuhair  in his poem is more like a contemplative than a poet, and that his morals are evident in the purposes of poetry that contained his commentary, and Zuhair was distinguished by honesty and the strength of emotion in Praise him, and that the moral aspect has taken reason, courage, justice and chastity as a frame and focus around which the outstanding one revolved, the study recommends that the suspended be addressed stylistically and linking that to the poet’s belief and his visions of life and the universe.
Keywords: the moral aspect; Zuhair's commentary; manifestations of moral values